2021
DOI: 10.1017/s147895152100167x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in end-of-life outcomes among advanced cancer patients in Sri Lanka: Results from the APPROACH study

Abstract: Objective A Universal Health Coverage goal is to provide access to affordable palliative care to reduce disparities in end-of-life (EOL) outcomes. To assess progress toward this goal in Sri Lanka, our primary aim was to systematically assess differences in patients’ physical, psychological, social and spiritual outcomes, and their perceived quality of care by their socioeconomic status (SES). Methods As part of the multi-country APPROACH (Asian Patient Perspectives Regarding Oncology Awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Esophagectomy was observed to be performed more frequently on high-SES patients with oesophageal cancer than on low-SES individuals. In contrast to cancer patients from higher SES groups, low SES cancer patients are more likely to experience higher mortality, depression, and other comorbidities, as well as a greater burden of symptoms [5]. Low SES cancer patients are also less likely to obtain palliative care and die at home [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esophagectomy was observed to be performed more frequently on high-SES patients with oesophageal cancer than on low-SES individuals. In contrast to cancer patients from higher SES groups, low SES cancer patients are more likely to experience higher mortality, depression, and other comorbidities, as well as a greater burden of symptoms [5]. Low SES cancer patients are also less likely to obtain palliative care and die at home [17].…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status was shown by few studies as an independent risk factor for death in cancer patients [22]. According to research by Hapurachi et al [22], patients with low SES reported lower physical, emotional, spiritual, and social EOL outcomes than those with high SES [5]. Following a diagnosis of advanced cancer, poor households in low-income countries are exposed to catastrophic health-related expenses, according to a prospective cohort research by Bates and colleagues [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in the largest government cancer hospital in Sri Lanka revealed that spiritual and psychological support services have not been used adequately by cancer patients who come from lowincome brackets (Hapuarachchi et al, 2021) compared to those patients who come from higher income brackets. Another study conducted on disabled veterans in Sri Lanka revealed that Buddhist religious activities, cultural activities, and support received from family and friends tend to reduce symptoms of depression and post-traumatic stress disorder (PTSD) (Zoysa & Wickrama, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%